Gender analysis of life aspiration among youth in Ogun State, Nigeria (2022)
Life aspiration is a great motivation to achieving any goal in life, when people settle with a certain aspiration, they have also decided their future. This study therefore focused on analysis of life aspiration of youth in Ogun State, Nigeria. A multi-stage sampling procedure was used to select 135 respondents for the study using Interview schedule as the instrument for data collection. Data were analysed using descriptive and inferential statistics such as chi-square, Pearson Product Moment Correlation and independent sample t-test. Result reveals that 56.3% of the respondents’ were male, the mean age of the respondents was 23.9years, male respondents (57.9%) had higher aspiration than female respondents (44.1%), respondents had more of intrinsic (73.40±11.66) aspiration than extrinsic (64.05±14.20). There was a significant relationship between parents’ occupation of the female respondents (p ≤ 0.05) and their life aspiration. Similarly, there was a significant relationship between father’s educational attainments of male respondents (p ≤ 0.05) and their life aspiration. Respondents were mostly motivated by their interest and ability, parental/guidance influence, educational level and were mostly constrained by inadequate finance, unemployment and inconsequential social network. This study concluded that life aspiration of youth was high. It was recommend that youth should be encouraged to pursue their interest and ability, attain higher educational level, and be granted easy access to finance, provision of empowerment and employment opportunities amongst others.